AN INVESTIGATION OF PLAGIARISM IN EFL THESIS GRADUATES OF ALMUSLIM UNIVERSITY - Zuhra, Intan; Nofriati, Eli; Dewi, Silvi Listia (Premise: Journal of English Education and Applied Linguistics, 2023)
Along with many plagiarism issues in the academic world, types of Plagiarism and its linguistic patterns are still under investigation. This study focuses on how Almuslim University EFL graduates perceive Plagiarism. The data for this study were gathered through documents and interviews using a descriptive qualitative design. Fifteen theses were used as samples to determine Plagiarism types and linguistic patterns, and 15 respondents were interviewed to determine the factors that influence Plagiarism. The documents were coded based on the types of Plagiarism, and the respondents were asked five questions during the interview. The findings revealed that 12 of the 15 theses samples had plagiarism rates greater than 25%, and three were found to have a small percentage of Plagiarism. According to the samples, most EFL graduates completed their theses using patchwriting instead of verbatim Plagiarism. In both types of Plagiarism (literal Plagiarism and intelligence).Furthermore, the interview results revealed that Plagiarism could occur due to various factors, including a lack of information, a desire to finish it quickly, an adverse environmental influence, and viewing the thesis as a graduate formality. Furthermore, the findings of this study can be used to educate others about the various types, causes, and contributing factors to Plagiarism. As a result, lecturers and universities can take precautionary measures to avoid Plagiarism in the future.